Gymnothorax baranesi, a new moray eel (Anguilliformes: Muraenidae) from the Red Sea - Smith, David G.; Brokovich, Eran; Einbinder, Shai (Zootaxa, 2008)
Gymnothorax baranesi n. sp. is described from three specimens collected in moderately deep water in the Gulf of Aquaba, Red Sea, Israel. It is characterized by irregular, pale, rosette-like spots on a dark background. The snout is somewhat slender. The intermaxillary teeth are arranged in one peripheral and one median row. The maxillary teeth are arranged in 1–2 rows, the inner row, when present, consists of only two depressible teeth. The new species is compared to other pale-spotted species in the Indian Ocean.